Refining the Application of Construal Level Theory: Egocentric and Nonegocentric Psychological Distances in Climate Change Visual Communication. Issue 1 (2nd January 2022) - Duan, Ran; Zwickle, Adam; Takahashi, Bruno
ABSTRACT: Recent studies have found mixed evidence about the role of psychological distance of climate change in people's engagement with the issue. To gain more clarity in the application of construal level theory of psychological distance in climate change communication, we used two online experiments to investigate how abstract and concrete construals of climate change imagery may differentially influence people's perceived psychological distances to the issue. Specifically, we clarified the conceptual differences between two subdimensions (i.e. egocentric and nonegocentric) of psychological distance and showed how the two types differ in climate change communication. Findings also showed that concrete construals of climate change images made participants estimate less egocentric geographical, temporal, and social distances to climate change, which led to greater mitigation behavioral intentions. But this construal-level effect did not exist when participants estimated the nonegocentric distances – the perceived distances between climate change and others (i.e. other locations, other people).